Pengawasan Sarana dan Prasarana Sekolah di Era Society 5.0 - Nur Rahma, Wahdania; Zulkarnain, Wildan; Sunarni, Sunarni (Universitas Negeri Malang, 2024)
Abstract: Various learning models in the era of society 5.0 must be supported by adequate facilities and infrastructure. School facilities and infrastructure are used to facilitate students' understanding of the material presented, by using appropriate educational facilities and infrastructure in teaching and learning activities to make them more effective and efficient. The Systematic Literature Review (SLR) method was chosen by the authors in this study, so that study materials related to the implementation of supervision of school facilities and infrastructure are in the form of books, articles and other sources that can be collected and conclusions drawn. . . This study resulted in the conclusion that, one aspect that is the main concern of educational supervision is related to educational facilities and infrastructure in schools. This research was conducted on the basis of the author's awareness of the importance of supervising school facilities and infrastructure in Era Society 5.0 in supporting learning activities so that they can run effectively and efficiently.Abstrak: Berbagai model pembelajaran di era society 5.0 harus ditunjang dengan sarana dan prasarana yang memadai. Sarana dan prasarana sekolah digunakan untuk mempermudah pemahaman siswa tentang materi yang disampaikan, dengan menggunakan sarana dan prasarana pendidikan yang tepat dalam kegiatan belajar mengajar di sekolah menjadi lebih efektif dan efisien. Metode Systematic Literature Review (SLR) dipilih oleh penulis dalam penelitian ini, sehingga bahan-bahan kajian yang berkaitan dengan pelaksanaan pengawasan sarana dan prasarana sekolah berupa buku, artikel dan sumber lainnya yang dapat terkumpul dan ditarik kesimpulan. Penelitian ini menghasilkan sebuah simpulan bahwa, salah satu aspek yang menarik perhatian utama dari pengawasan pendidikan adalah terkait sarana dan prasarana pendidikan yang ada di sekolah. Penelitian ini dilakukan atas dasar, penulis menyadari tingkat urgensitas pengawasan sarana dan prasarana sekolah di Era Society 5.0 dalam menunjang kegiatan pembelajaran agar dapat berjalan secara efektif dan efisien.